2016
DOI: 10.1161/jaha.115.002716
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic Recanalization of Carotid Arteries Is Highly Dependent on Degree of Stenosis, Despite Sonothrombolysis

Abstract: BackgroundStroke associated with acute carotid occlusion is associated with poor effectiveness of tissue plasminogen activator (tPA) thrombolysis and poor prognosis. Rupture of atherosclerotic plaques resulting in vascular occlusions may occur on plaques, causing variable stenosis. We hypothesized that degree of stenosis may affect recanalization rates with tPA. Ultrasound+tPA (sonothrombolysis) has been shown to improve recanalization for intracranial occlusions but has not been tested for carotid occlusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Following adjustment for the effect of confounding variables, hormonal replacement therapy, obesity, history of a previous TIA, and anti-depressant use were factors found to be associated with inclusion for rtPA in the past-TIA patients, while increasing age, female gender, carotid artery stenosis, diabetes, history of previous Student's T test * P-value < 0.05 stroke and alcohol use, cholesterol, serum creatinine, INR, and increased systolic blood pressure were associated with exclusion from rtPA. The identified comorbidities associated with exclusion from thrombolytic therapy are comparable to existing prospective and retrospective studies, such as increasing age associated with worse outcomes [32], female gender corresponding with significantly higher percentages of cardioembolic strokes [33], and severe carotid artery stenosis, which predicts poor outcome [34]. Other identified comorbidities reported in previous studies are diabetes; due to hyperglycemia, which increases the risk of cerebral hemorrhage with rtPA treatment [35], and chronic alcohol use; which increases excitotoxic/ischemic damage, leading to poor outcomes [36].…”
Section: Discussionsupporting
confidence: 55%
“…Following adjustment for the effect of confounding variables, hormonal replacement therapy, obesity, history of a previous TIA, and anti-depressant use were factors found to be associated with inclusion for rtPA in the past-TIA patients, while increasing age, female gender, carotid artery stenosis, diabetes, history of previous Student's T test * P-value < 0.05 stroke and alcohol use, cholesterol, serum creatinine, INR, and increased systolic blood pressure were associated with exclusion from rtPA. The identified comorbidities associated with exclusion from thrombolytic therapy are comparable to existing prospective and retrospective studies, such as increasing age associated with worse outcomes [32], female gender corresponding with significantly higher percentages of cardioembolic strokes [33], and severe carotid artery stenosis, which predicts poor outcome [34]. Other identified comorbidities reported in previous studies are diabetes; due to hyperglycemia, which increases the risk of cerebral hemorrhage with rtPA treatment [35], and chronic alcohol use; which increases excitotoxic/ischemic damage, leading to poor outcomes [36].…”
Section: Discussionsupporting
confidence: 55%
“…In addition, our finding that AIS patients without HF that present with coronary artery stenosis, history of previous stroke, and elevated lipid levels, INR, creatinine, and heart rate was more likely not to receive rtPA is consistent with other studies demonstrating the association between rtPA and elevated heart rate, 28 lipid levels, 29 INR, 30 creatinine, 31 coronary artery stenosis, 32 and previous stroke. 29 Estimates of eligibility for rtPA in the AIS population are reported to range from 6% to 8% of all strokes.…”
Section: Discussionsupporting
confidence: 91%
“…Experimental studies have demonstrated a strong relationship between the degree of ipsilateral carotid stenosis and thrombolytic recanalization during AIS, showing a very low rate of recanalization for stenosis > 70% ( 11 ). The Interventional Management of Stroke (IMS)-III study showed that patients with an ICS > 70% presented a significantly longer mean time to reperfusion after endovascular treatment, whereas mTICI scores, 90-day mRS scores, or major complications, such as cerebral bleeding rates, did not show a significant difference from the group with non-significant stenosis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%